2023
DOI: 10.1038/s41467-023-37137-0
|View full text |Cite
|
Sign up to set email alerts
|

UNC-43/CaMKII-triggered anterograde signals recruit GABAARs to mediate inhibitory synaptic transmission and plasticity at C. elegans NMJs

Abstract: Disturbed inhibitory synaptic transmission has functional impacts on neurodevelopmental and psychiatric disorders. An essential mechanism for modulating inhibitory synaptic transmission is alteration of the postsynaptic abundance of GABAARs, which are stabilized by postsynaptic scaffold proteins and recruited by presynaptic signals. However, how GABAergic neurons trigger signals to transsynaptically recruit GABAARs remains elusive. Here, we show that UNC-43/CaMKII functions at GABAergic neurons to recruit GABA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 78 publications
0
9
0
Order By: Relevance
“…Endophilin is a membrane-associated protein that is required for SVs endocytosis ( Ringstad et al, 1999 ; Schmidt et al, 1999 ; Schuske et al, 2003 ). We used CRISPR/Cas9 system to insert a sequence encoding seven GFP11 fragments at the C-terminus of UNC-57/endophilin ( Hao et al, 2023 ). In parallel, the GFP1-10 fragment was constitutively expressed in DA and DB cholinergic motor neurons or GABAergic motor neurons under the control of the unc-129 or unc-25 promoters, respectively ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Endophilin is a membrane-associated protein that is required for SVs endocytosis ( Ringstad et al, 1999 ; Schmidt et al, 1999 ; Schuske et al, 2003 ). We used CRISPR/Cas9 system to insert a sequence encoding seven GFP11 fragments at the C-terminus of UNC-57/endophilin ( Hao et al, 2023 ). In parallel, the GFP1-10 fragment was constitutively expressed in DA and DB cholinergic motor neurons or GABAergic motor neurons under the control of the unc-129 or unc-25 promoters, respectively ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…S3, A and B ). Here, we focused our attention on UNC-43/CaMKII since it plays important roles in synaptic transmission and regulates the abundance of DCVs and SVs ( Hao et al, 2023 ; Hoover et al, 2014 ; Liu et al, 2007 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Little is known about the role of presynaptic CaMKII in GABAergic synapse organization. A recent study has shown that, at Caenorhabditis elegans ( C. elegans ) neuromuscular junctions, presynaptic CaMKII (UNC-43, the C. elegans sole ortholog of CaMKII) trans-synaptically regulates postsynaptic GABA receptor recruitment by up-regulating presynaptic Nrxn surface delivery together with enhanced secretion of MADD-4B/Punctin ( Hao et al, 2023 ), which makes a protein complex with Nrxn1 and Nlgn1 ( Maro et al, 2015 ). Future studies with interneuron type-specific genetic manipulation of CaMKII and Src-mediated signaling pathways will be important to address how these pathways are linked with Nrxns in presynaptic terminals of each type of interneuron and define their GABAergic synapse specificity in developing mammalian brain circuits.…”
Section: Discussionmentioning
confidence: 99%